Rekonstruksi Peran Masjid: Lebih dari Sekedar Tempat Ibadah: Reconstructing the Role of Mosques: More than Just Places of Worship - Umairoh Risa Aulia; Hadi Dharma; Nur Haniyah; Rani Selviani; Ammamiarihta, Ammamiarihta (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
Since the time of Prophet Muhammad saw. mosques have served multiple functions beyond worship, acting as centers of learning, social interaction, and community empowerment. In the modern era, however, their roles are often reduced to ritual activities alone. This study seeks to reframe the function of mosques in accordance with contemporary needs, taking Baiturrahim Mosque in Nogorejo Village, Galang District, Deli Serdang, as a case study. Employing a qualitative phenomenological approach through observation and interviews, the research reveals that while Baiturrahim Mosque contributes significantly to the spiritual and social life of the community, its broader role remains limited. Key challenges include fostering children’s moral development and maintaining cleanliness within the mosque environment. The findings highlight the necessity of professional mosque management, child-friendly programs, and greater community involvement to revitalize its educational, social, and religious roles. By adopting an inclusive and adaptive reconstruction, mosques can once again function as transformative centers for both spiritual growth and social development in contemporary society.